Development-induced water pollution in Malaysia: policy implications from an econometric analysis - Muyibi,, Suleyman A.; Ambali, Abdul Rauf; Eissa, Garoot Suleiman (IWA Publishing, 2008)

(untitled)
This paper evaluates the development-induced water pollution in Malaysia within an econometric framework. It explores the relationship between water pollution problems and rapid economic development such as industrial growth and urbanization/population in the country. Methodologically, a Multiple Regression Analysis that is essential to reveal the likely hidden interactive effects between the multivariate pollutants from different sources on river catchments was employed. The main objectives of the paper are (a) to spell out the structure and regional pattern of water pollution issues in Malaysia; (b) to find the hidden interactive effects of point and non-point sources of water pollutants on rivers; and (c) to turn the attention of water policy-makers to the implication of such interactive effects, which may jeopardize the administrative enforcement actions of minimizing water pollution issues in any given country. The paper, therefore, argues that if the abatement policy instruments are stringently controlling only water pollutants from one single source, policy abatement programs designed for controlling water pollution would not be effective. This paper has concluded that the imposition of appropriate treatment technology in industries is strongly needed to solve the problem of water pollution. People awareness of water pollution programs, and public and private sector participation are prerequisites that must always reflect in every stage of policy control and design by the authority